2009
DOI: 10.1037/a0016455
|View full text |Cite
|
Sign up to set email alerts
|

Causality and cross-modal integration.

Abstract: Schutz and Lipscomb (2007) reported an audiovisual illusion in which the length of the gesture used to produce a sound altered the perception of that sound's duration. This contradicts the widely accepted claim that the auditory system generally dominates temporal tasks because of its superior temporal acuity. Here, in the first of 4 experiments, we show that impact gestures influence duration ratings of percussive but not sustained sounds. In the 2nd, we show that the illusion is present even if the percussiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
63
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 85 publications
(131 reference statements)
7
63
0
Order By: Relevance
“…This finding is consistent with previous research demonstrating that visual information does not affect auditory judgments of event duration (Walker & Scott, 1981). However, these same participants were unable to ignore visual information when judging the duration of percussive tones, a finding consistent with earlier sensory integration experiments involving percussive sounds (Schutz & Kubovy, 2009b;Schutz & Lipscomb, 2007). This finding suggests that patterns of integration widely agreed upon (previously assessed primarily with flat tones) might not apply to real world sounds with natural decays.…”
Section: Amplitude Envelope Affects Experimental Outcomessupporting
confidence: 82%
“…This finding is consistent with previous research demonstrating that visual information does not affect auditory judgments of event duration (Walker & Scott, 1981). However, these same participants were unable to ignore visual information when judging the duration of percussive tones, a finding consistent with earlier sensory integration experiments involving percussive sounds (Schutz & Kubovy, 2009b;Schutz & Lipscomb, 2007). This finding suggests that patterns of integration widely agreed upon (previously assessed primarily with flat tones) might not apply to real world sounds with natural decays.…”
Section: Amplitude Envelope Affects Experimental Outcomessupporting
confidence: 82%
“…One would perhaps expect the preparatory height to have an influence on the multisensory information. Interestingly enough, a later study showed the gesture after the actual impact to be more important for how long the notes were rated to be [22]. Thus, although a percussionist cannot prolong the played note as such, the long gesture after impact can still make it sound longer.…”
Section: Visual Communicationmentioning
confidence: 99%
“…The perceived duration of the sound is longer if the gesture is long than if is short [18,19]. Schutz & Kubovy [18] demonstrated that this effect was due to cross-modal causality, by first showing that the effect depended on the percussive element of the sound. For example, when the sound associated with the long and short gestures (marimba or piano), the effect was present.…”
Section: Bindingmentioning
confidence: 99%